Knowledge Gap and Path Analysis of Adoption of Makhana (Euryale Ferox Salisb) Growers in Bihar - Kumar Sonu,; Kaushal Kumar Jha, (Indian Journal of Extension Education, 2025)
This study examined the knowledge gap and adoption of the improved makhana cultivation technology in Bihar. The research utilized a descriptive research design and focused on four districts viz. Purnia, Katihar, Darbhanga, and Madhubani. During 2022–24, eight villages were purposively selected from these blocks which included Pipra and Birpur from Purnea block, Mirzapur and Lachhmipur from Barari block, Ballupur and Kishunpur from Bhadurpur block, and Chanuraganj and Simra from Jhanjharpur block. The study included 120 sample, with fifteen makhana growing farmers randomly chosen from each of the eight villages. The findings revealed that plant protection component (disease and pest control) had the highest mean knowledge gap (61.88%), with a relatively low knowledge index of 24.10, and adoption index of 19.33. Further technology adoption and knowledge level of farmers had positive and significant association with landholding size, annual income, income from makhana and training exposure. Improvement in information dissemination on latest technical knowhow via focused campaigns and farmer engagement activities through need based trainings is crucial for increasing the adoption of improved makhana cultivation technology among the farmers for enhanced productivity and profitability.